2010
DOI: 10.1002/9780470151808.sc01e05s12
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Amniotic Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) have the ability to differentiate into osteocytes, chondrocytes, and adipocytes and possess immunomodulatory properties. Amniotic membrane from human term placenta is a potential source of multipotent MSCs that could be useful for regenerative medicine. This unit describes a detailed and simple protocol for the isolation of amniotic mesenchymal cells. We also introduce a simple density separation technique for the purification of this cell type from possible contamination with amn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 8 publications
1
37
0
1
Order By: Relevance
“…AM-MSCs were isolated according to Marongiu et al [23] and Kita et al [24] with modifications. Briefly, the AM was weighted, washed, and cut into pieces.…”
Section: Isolation Of Mscs From Uc Am and Bmmentioning
confidence: 99%
“…AM-MSCs were isolated according to Marongiu et al [23] and Kita et al [24] with modifications. Briefly, the AM was weighted, washed, and cut into pieces.…”
Section: Isolation Of Mscs From Uc Am and Bmmentioning
confidence: 99%
“…Cells from mesenchymal and epithelial amniotic layers, amniotic mesenchymal stromal and amniotic epithelial cells (AEC), respectively, can be obtained without any ethical concerns, in large amounts and with validated protocols [38], [39]. Amnion derived cells have been shown to maintain a remarkable plasticity and to possess a high self-renewing capacity [40][45].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that different inducing factors could affect the direction of differentiation of the AMSCs and that the AMSCs that originate from mesoblastema could differentiate into ectoderm and endoderm cell types. The autologous nature of these stem cells, together with their putative multi-potentiality and convenient procurement, makes them an excellent option for future tissue engineering and cell-based therapies (Marongiu et al 2010).…”
Section: Discussionmentioning
confidence: 99%